2016
DOI: 10.3892/mmr.2016.5894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of celastrol on enhancing apoptosis of ovarian cancer cells via the downregulation of microRNA-21 and the suppression of the PI3K/Akt-NF-κB signaling pathway in an in vitro model of ovarian carcinoma

Abstract: Abstract. Celastrol has previously been used to treat rheumatoid arthritis, bruises, back pain and additional diseases. At present, efficacy studies predominantly focus on the anti-inflammatory, antioxidative and antitumor effects of celastrol. However, the effect of celastrol on ovarian cancer cells is not fully elucidated. In the present study, the effects of celastrol were investigated in ovarian cancer cells and the mechanisms involved were explored. In OVCAR3 cells, celastrol was observed to suppress cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…In fact, some scholars reported that down-regulation of miR-21 inhibited PI3K/Akt-NF-κB signaling pathway and promoted apoptosis in OVCAR3 cells. 51 This was consistent with our study that HUMSC-Exos underexpressed miR-21a-3p, synchronizing with p65 inactivation and inhibited cell viability in fibroblasts. In contrast, some scholars found that after treatment with miR-21 mimic-loaded human peripheral blood-derived exosomes, gene expression levels of mothers against decapentaplegic homolog 3 (Smad7), phosphatase and tension homologue (PTEN) and matrix metalloproteinase 2 (MMP2) associated with cardiac fibrosis increased both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, some scholars reported that down-regulation of miR-21 inhibited PI3K/Akt-NF-κB signaling pathway and promoted apoptosis in OVCAR3 cells. 51 This was consistent with our study that HUMSC-Exos underexpressed miR-21a-3p, synchronizing with p65 inactivation and inhibited cell viability in fibroblasts. In contrast, some scholars found that after treatment with miR-21 mimic-loaded human peripheral blood-derived exosomes, gene expression levels of mothers against decapentaplegic homolog 3 (Smad7), phosphatase and tension homologue (PTEN) and matrix metalloproteinase 2 (MMP2) associated with cardiac fibrosis increased both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, we have demonstrated that celastrol mediated dose-dependent anti-growth effects on human ovarian cancer cell lines SKOV3 and A2780. The IC 50 value after 72 h treatment with celastrol ranged from 2 to 3 μM in these two human ovarian cancer cell lines, similarly to the IC 50 value of celastrol of ovarian cancer in other articles (15, 16). We have also shown that celastrol induced both the early and late stage of apoptosis and cell cycle arrest in G2/M phase with obvious up-regulation of cleaved-PARP, pp38 T180/Y182, pJNK T183/Y185, p27 and Cyclin B1 and down-regulation of pERK T202/Y204, pAKT S473, RAF1 and Cyclin E in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 69%
“…For the treatment of ovarian cancer, triptolide has been shown to inhibit the proliferation, migration and invasion of ovarian cancer in multiple pathways (2931) and demonstrated to exert efficacy in preclinical models (32). Celastrol has also been reported to induce apoptosis and inhibit proliferation, migration and invasion in ovarian cancer cells in vitro (14, 16), but the mechanism for its anti-tumor effect and the effect of celastrol on the growth of ovarian cancer cells in vivo are not fully understood. In our present study, we have demonstrated that celastrol mediated dose-dependent anti-growth effects on human ovarian cancer cell lines SKOV3 and A2780.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a few molecules or signal pathways were reported to be involved in the anti-cancer mechanisms of celastrol. [4][5][6] For example, celastrol down-regulated phosphatidylinositol 3-kinase (PI3K)/Akt/ nuclear factor-kappaB (NF-κB) signaling pathway in osteosarcoma and ovarian cancer cells 7,8) ; celastrol was reported to suppress the invasion and metastasis of colon cancer cells through down-regulating the expression of CXCR4 chemokine receptor, 9) yet other mechanisms of celastrol against colon cancer are still not fully elucidated.…”
mentioning
confidence: 99%